Pass the mic: identity and agency in child and youth care environments - Berikoff, Ahna; Reed, Kelsey (My University, 2019)
Beginning with this issue, RCYCP has invited participants in the Write On and Pass the Mic project to share their work. Individuals taking part in this writing/podcast project - are students and post-grads from the Bachelor of Child and Youth Care at MacEwan University, Alberta, Canada. They are the sharers of knowledge; the storytellers. As supporters of this project providing gentle guidance, we both recognize the integral role of storytellers to inform, challenge, exchange and learn collectively. We have the privilege of being with these individuals as they share with openness and vulnerability the dimensionality of their identities and experiences. They share with intimacy, transparency and poignancy. As a starting point we, supporters of this project, invite you into our stories communicating who we are and where we are from along the passages of our ancestry.